2019
DOI: 10.1002/prep.201900278
|View full text |Cite
|
Sign up to set email alerts
|

Boron Carbide Based Biocide Compositions: A Study of Iodate Particle Size on Combustion and Iodine Output

Abstract: The ever‐present threat of biological weapons has encouraged the development of novel pyrotechnic formulations that release gaseous iodine upon combustion, which acts as a potent active agent capable of countering bio‐agents (e. g. anthrax). These formulations typically contain a fuel (Al, B, Al/B4C) and an iodate serving as an oxidizer. However, the percentage of free iodine generated is relatively low and aging of these formulations remains an issue. In this work, the role of particle size on the combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Al, B, Ti). 16 While fluoropolymers have been used as oxidizers in energetic materials, there has been limited research on how the electromechanical properties influence the combustion properties. [15][16][17][18] Specifically, tuning the impact sensitivity, burning rate and other combustion properties in fluoropolymer bound energetics by using piezoelectricity and flexoelectricity has yet to be fully studied.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Al, B, Ti). 16 While fluoropolymers have been used as oxidizers in energetic materials, there has been limited research on how the electromechanical properties influence the combustion properties. [15][16][17][18] Specifically, tuning the impact sensitivity, burning rate and other combustion properties in fluoropolymer bound energetics by using piezoelectricity and flexoelectricity has yet to be fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…16 While fluoropolymers have been used as oxidizers in energetic materials, there has been limited research on how the electromechanical properties influence the combustion properties. [15][16][17][18] Specifically, tuning the impact sensitivity, burning rate and other combustion properties in fluoropolymer bound energetics by using piezoelectricity and flexoelectricity has yet to be fully studied. Initial research by Row and Groven 15 reported a significant change in the impact sensitivity when a DC voltage was applied to the PVDF/Al and THV/Al reactive systems indicating the electroactive nature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the particle size of the reactive solids, whether the fuel or oxidizer, can greatly influence the overall system. While many studies have focused on the fuel particle size for pyrotechnic and propellant systems [1][2][3][4][5][6], few have studied the oxidizer particle size directly for use in pyrotechnics [7][8][9][10][11]. Overall, the consensus from the fuel studies is that as the fuel (aluminum, zirconium, boron, magnesium, etc.)…”
Section: Introductionmentioning
confidence: 99%